Microwave Irradiation of PC3 Cells at Constant Culture Temperature Alters the Incorporation of BODIPY into Cells and Reduction of MTT. Issue 26 (12th September 2017) - Mazinani, Sina Atrin; Moradi, Fereshteh; Stuart, Jeffrey A.; Yan, Hongbin
Abstract: The present study investigated the impact of 10 W microwave irradiation at 2.45 GHz on the cell viability and membrane properties of human prostate cancer PC3 cells, while the temperature of the cell cultures was maintained at 37±2 °C through simultaneous cooling. Microwave irradiation under these conditions did not induce apoptosis, nor otherwise lead to loss of cell viability, as indicated by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT), Annexin–V, and propidium iodide assays. Interestingly however, incorporation of BODIPY (4, 4‐difluoro‐5‐methyl‐4‐bora‐3a, 4a‐diaza‐ s ‐indacene) 3‐dodecanoic acid into the cell membrane was facilitated by microwave treatment at constant temperature. Also, constant temperature microwave treatment significantly increased the rate of reduction of MTT. Taken together, these results suggest that constant temperature microwave, while non‐lethal to PC3 cells, may alter membrane properties. Abstract : Exposure of human prostate cancer cells to non‐lethal microwave irradiation (2.45 GHz) at a constant culture temperature did not result in apoptosis or changes in cell viability, however, the microwave treatment led to increases in the extent of incorporation of a BODIPY fatty acid into cell membranes, and facilitated the reduction of 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) into the corresponding formazan.